Forest and forest fuels evaluation in Pinus hartwegii forests of the State of Mexico, in relation to cover densities and fire vulnerability - Castañeda Rojas, Mario Fermin; Endara Agramont, Angel Rolando; Villers Ruiz, María de Lourdes; Nava Bernal, Eufemio Gabino (Instituto de Ecología, A.C., 2016)
A forest evaluation in relation to dead wood fuel materials quantity and quality in Pinus hartwegii forests was made, in order to show vulnerability conditions and fire propensity. Based on a multispectral satellite images (2010) interpretation, 23,685 ha of P. hartwegii forest in the State of Mexico were grouped in three forest cover classes. A forest inventory, human activity presence, forest fuels and physical parameters measurements were carried out in 30 circular plots of 1,000 m2. Forest fuels quantity and types were assessed following a planar intersect method. Basal area, forest biomass and vertical structure were also measured per site and cover class. The results show differences between the three categories concerning, tree densities coverage (ind ha-1) basal area (m2) and amount of biomass (t ha-1) as well as the vertical structure of forests. Higher quantity of forest fuels occurs in fragmented forests (33.81 t ha-1), of high diameter classes mainly (from 2.5 cm to 7.5 cm, and ≥ 7.5 cm diameter), where fire resides longer in times of a conflagration. Human activities in these areas trigger this situation, a risk that has to be addressed in the area. The application of this methodology could be used in bigger areas of any other forest ecosystem, allowing the determination of the living environment and vulnerability areas, providing useful elements for Integrated Fire Management (IFM) programs.